Pelaksanaan Pemulihan Aset Oleh Jaksa Pada Tindak Pidana Korupsi Berdasarkan Undang-Undang Nomor 11 Tahun 2021 Tentang Kejaksaan Republik Indonesia - Butarbutar, Andika Demto; Ridwan, Ridwan; Rofiana, Reine (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2024)
Introduction: Asset recovery in corruption cases has not been maximized in its implementation, this can be seen from existing cases, asset recovery from state losses incurred is still not maximum, this can be proven in Indonesian records. The prosecutor as a law enforcer has the authority to recover assets by carrying out activities to trace, confiscate and return assets obtained from criminal acts as regulated in Article 30A of Law Number 11 of 2021 concerning the Prosecutor's Office of the Republic of Indonesia. Purposes of the Research: to find out how the implementation of asset recovery carried out by the prosecutor in resolving corruption crimes? and What are the problems of the prosecutor in recovering assets from the proceeds of corruption crimes? Methods of the Research: The research method used in this article is in the form of normative juridical, The specifications in this article are descriptive-analytical. Results of the Research: The results of the research obtained by the author are that in the implementation of asset recovery carried out by the Prosecutor's Office, there are two methods carried out by the prosecutor in carrying out asset recovery, namely the investigation method and the asset tracking method, and the author finds various problems owned by the prosecutor in carrying out asset recovery. The conclusion is that in the implementation of the recovery of the prosecutor's assets, it has not been maximized to the return of state losses.